Multiple, consecutive, fully‐extended 2.05‐helix peptide conformation. Issue 6 (November 2013) - Peggion, Cristina; Moretto, Alessandro; Formaggio, Fernando; Crisma, Marco; Toniolo, Claudio; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT The peptide 2.05‐helix does exist. It has been experimentally authenticated both in the crystalline state (by X‐ray diffraction) and in solution (by several spectroscopic techniques). It is the most common conformation for Cα‐tetrasubstituted α‐amino acids with at least two atoms in each side chain, provided that cyclization on the Cα‐atom is absent. X‐Ray diffraction has allowed a detailed description of its geometrical and three‐dimensional (3D)‐structural features. The infrared absorption and the nuclear magnetic resonance parameters characteristics of this multiple, consecutive, fully‐extended structure have been described. Conformational energy calculations are in agreement with the experimental findings. As the contribution per amino acid residue to the length of this helix is the longest possible, its exploitation as a molecular spacer is quite promising. However, it is a rather fragile 3D‐structure and particularly sensitive to solvent polarity. Interestingly, in such a case, it may reversibly convert to the much shorter 310‐helix, thus generating an attractive molecular spring. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 621–636, 2013.